1997
DOI: 10.1021/ed074p330
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simultaneous-Synchronized Macroscopic, Microscopic, and Symbolic Representations To Enhance the Teaching and Learning of Chemical Concepts

Abstract: A prototype multimedia program, Multimedia and Mental Models in Chemistry (4M:CHEM), was developed to facilitate student learning in the classroom. 4M:CHEM utilizes a computer split-screen design to show simultaneous videos of real experiments, molecular-level animations of these experiments, real time graphs of macroscopic properties or structural diagrams, and chemical equations. These four windows can be shown individually or in any combination. When multiple windows are activated, actions in each are synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
12

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 14 publications
2
85
0
12
Order By: Relevance
“…Equally important, students need to master certain abilities and skills such as visualizing a chemical reaction at the molecular level, reasoning about a macroscopic phenomenon using chemical representations, and coordinating multiple representations (Ben-Zvi, Eylon, & Silberstein, 1987;Gabel & Samuel, 1987;Hesse & Anderson, 1992;Kozma, 2000Kozma, , 2003Krajcik, 1991;Yarroch, 1985). Finally, students need to develop a coherent conceptual framework that integrates their knowledge and skills to establish a scientiÞc theory of the entities and processes that underlie a given observed phenomenon (Kozma, Russell, Jones, Marx, & Davis, 1996;Russell et al, 1997). For example, although Nakhleh et al (2005) found that more than half of the nine middle school students they interviewed had some understanding of the particulate nature of matter, their conceptual framework was rather fragmented.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Equally important, students need to master certain abilities and skills such as visualizing a chemical reaction at the molecular level, reasoning about a macroscopic phenomenon using chemical representations, and coordinating multiple representations (Ben-Zvi, Eylon, & Silberstein, 1987;Gabel & Samuel, 1987;Hesse & Anderson, 1992;Kozma, 2000Kozma, , 2003Krajcik, 1991;Yarroch, 1985). Finally, students need to develop a coherent conceptual framework that integrates their knowledge and skills to establish a scientiÞc theory of the entities and processes that underlie a given observed phenomenon (Kozma, Russell, Jones, Marx, & Davis, 1996;Russell et al, 1997). For example, although Nakhleh et al (2005) found that more than half of the nine middle school students they interviewed had some understanding of the particulate nature of matter, their conceptual framework was rather fragmented.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…One reason why students may have difficulty with the concepts of diffusion, osmosis and active transport is that these concepts require students to visualize and think about chemical processes at the molecular level (Johnstone & Mahmoud, 1980;Friedler et al, 1987;Westbrook & Marek, 1991). Studies have shown that instruction involving computer animations can facilitate the students thinking about chemical processes at the molecular level (Williamson & Abraham, 1995;Russel et al, 1997;Sanger & Greenbowe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Application of multimedia in education through World Wide Web, CD-ROMs, DVD and virtual reality can help students visualize the abstract concepts especially in the learning of chemistry. The use of multimedia creates the environment where students can visual the abstract chemical processes via animation and video in macroscopic, microscopic and symbolic levels (Bowen, 1998;Burke et al 1998;Rodrigues et al 2001;Russell et al 1997). Studies (Doymus, 2010;Gois & Giordan, 2009;Lerman & Morton, 2009) have been carried out and results showed that animation and simulation using ICT can help students to visualize and hence enhance students' understanding in learning abstract chemistry topics.…”
Section: The Use Of Ict In Teaching and Learningmentioning
confidence: 99%
“…Students can visualize (Lerman, 2001) the whole process through the animations in Micro-World. IMMPA EC Lab makes the abstract concepts 'concrete' because students can watch the whole process visually at three representation levels (Bowen 1998;Burke et al 1998;Rodrigues et al 2001;Russell et al www.intechopen.com 1997). Hence, students learning Electrochemistry with animations and simulations in multimedia module will gain higher achievements compared to traditional method (Hasnira, 2005;Sanges & Greenbowe, 2000).…”
Section: The Chlorine Gas Is Produced (Kl29)mentioning
confidence: 99%